Effects of numerical unbalance constraints on workload and tactical individual actions during ball possession small-sided soccer games across different age groups - Nunes, Nuno (2021)
This study aimed to examine the effects of age group (under-11, under-15, and under-23) on the external, internal workloads, and tactical individual actions when playing 4v2, 4v4, and 4v6 ball possession small-sided soccer games. Data were analysed separately under the opponent perspective (4vX) and by the cooperation perspective, according to teammates (4v2+X). For all opponent formats, statistical differences were found for walking, with older age groups covering longer distances. Higher running distances were found in 4v4 game format for U11s, while U23s reported higher RPE scores in 4v4 and 4v6 formats. More passes were performed in 4v2 and 4v4 game formats for U11s and a higher maximum passing speed in 4v6 format for U15s and U23s. In the cooperation perspective, statistical differences were found for all external workload variables: U11s covered more distances while sprinting, whereas U23s walked more, perceiving the task as more intense. Similarly, U11s performed a higher amount of tactical individual actions also in every format. Younger players seem to benefit from a lower level of opposition to mature tactical individual actions, while older players can develop fast ball circulation in numerical inferiority.